Elective home education of children with neurodevelopmental conditions before and after the COVID-19 pandemic started - Paulauskaite, Laura; Timmerman, Amanda; Kouroupa, Athanasia; Allard, Amanda; Gray, Kylie M.; Hastings, Richard P.; Heyne, David; Melvin, Glenn A.; Tonge, Bruce; Totsika, Vasiliki (Frontiers in Psychology, 2022)
COVID-19 brought disruptions to children’s education and mental health, and accelerated school de-registration rates. We investigated Elective Home Education (EHE) in families of children with a neurodevelopmental condition. A total of 158 parents of 5-15 year-old children with neurodevelopmental conditions (80% autistic) provided information on reasons for de-registration, their experience of EHE, and children’s mental health. Few differences were found between children participating in EHE before and after the pandemic started. Low satisfaction with school for not meeting children’s additional needs was the main reason for de-registering in both groups. COVID-19 had a more limited role in parents’ decision to de-register. The main advantage of EHE reported in both groups was the provision of personalised education and one-to-one support. Levels of anxiety, internalising and externalising problems were similar between children participating in EHE before and after the pandemic started, and also similar between all children in EHE and school-registered children (N=1,079).